Vascular Dysfunction in Mother and Offspring During Preeclampsia: Contributions from Latin-American Countries - Giachini, Fernanda Regina (2017)
Pregnancy is a physiologically stressful condition that generates a series of functional adaptations by the cardiovascular system. The impact of pregnancy on this system persists from conception beyond birth. Recent evidence suggests that vascular changes associated with pregnancy complications, such as preeclampsia, affect the function of the maternal and offspring vascular systems, after delivery and into adult life. Since the vascular system contributes to systemic homeostasis, defective development or function of blood vessels predisposesboth mother and infant to future risk for chronic disease. These alterations in later life range from fertility problems to alterations in the central nervous system or immune system, among others. It is important to note that rates of morbi-mortality due to pregnancy complications including preeclampsia, as well as cardiovascular diseases have a higher incidence in Latin American countries than in more developed countries. Nonetheless, there is a lack both in the amount and impact of research conducted in Latin America. An impact, althoughsmaller, can be seen when research in vascular disorders related to problems during pregnancy is analyzed. Therefore, in this review, information about preeclampsia and endothelial dysfunction generated from researchgroups based in Latin American countries will be highlighted. We relate the need, as present in many other countries in the world, for increased effective regional and international collaboration to generate new dataspecific to our region on this topic.